The benefits of career development through e-learning - Marinković, Milos; Milasinović, Danko (Hotel and Tourism Management, 2013)
This paper presents the advantages of e-learning compared to traditional learning in the career development. Recent studies have shown that most new jobs require skills that only minority of the workforce possess. In such environment, the process of lifelong learning becomes essential. In career development, people usually cannot be observed as students in a classical way because of their workplace responsibilities. The transfer of the learnt to the workplace thus becomes most important. E-learning is a method of education which includes self-motivation, communication, efficiency and technology. This method of learning involves online courses. The knowledge students gain from these courses is immediately applicable to daily activities at a workplace. Students have positive attitudes towards the use of e-learning for personal training and development. This approach also brings the new motivation for performing daily activities at the workplace. The adjustment of study programs to this type of education could establish a synergy between universities and companies. The need of companies should drive development of online courses at institutions that provide e-learning. When the implementation of learning management system into business organizations and faculties is discussed, open source software is often the first choice. From our point of view that should be considered as a good choice.